Higher mental illness-related stigma after receiving mental health service among adolescents and youth with depressive symptoms in Chongqing, China - Liu, Yi-Hao; Luo, Jian-Jun; Wang, Cong; Yang, Yi-Yue; Zhou, Lie; Jin, Hui; Xiao, Yun; Wen, Yang; Ahmad, Jawad; Ran, Michelle Yu-Xin; Du, Na; Cai, Jia; et al. (Frontiers in Psychiatry, 2026)
BackgroundPrevious evidence suggests that some adolescent and youth students with depressive symptoms may access mental health services only once but never return for follow-up care. The current study aims to investigate whether adolescent and youth students with depressive symptoms experience increased mental illness-related stigma after receiving mental health services within the past 12 months and explore potential sex and ethnicity differences.MethodA cross-sectional online survey was conducted among adolescents and early youth attending schools in Chongqing, China (age 11–24) through convenience sampling, between November 2024 and February 2025. Participants reported their demographic information, depressive symptoms (PHQ-9), anxiety symptoms (GAD-7), mental health services received in the past 12 months, and mental illness-related stigma (PDD). Data was analysed with ANOVA and simple slope analysis.ResultsIn total, 33,409 students completed the survey (mean age: 16.27 ± 2.45; female = 49.6%), with 43.6% reporting depressive symptoms. Among students with depressive symptoms (mean age: 15.95 ± 2.21; female = 54.4%), only 8.9% reported mental health services use. Overall, mental health service use was not significantly associated with mental illness-related stigma, F(1, 14568) = 1.27, p = .259, ηp2 = .000. However, a significant interaction was seen between mental health service use and sex, F(1, 14569) = 8.69, p = .004, ηp2 = .001. Simple slopes analysis indicated that sex moderated the relationship between mental health services use and stigma, R2 = .008, F(10, 14568) = 11.21, p <.001, where mental health service use was associated with greater stigma among female students (p <.001), but not among male students (p = .527).ConclusionsThese findings indicate that a substantial treatment gap for depressive symptoms persists among adolescents and students in Chongqing, China. Notably, among female students, mental health service use in the past 12 months was associated with heightened mental illness-related stigma. This underscores the need for interventions that specifically address stigma in the context of mental health service use.